Quality of life after pancreas transplantation: time to look again. Issue 4 (August 2019) - Hanlon, Matthew; Cooper, Matthew; Abrams, Peter
Abstract : Purpose of review: To summarize the existing body of literature regarding quality of life after pancreas transplantation, discuss the limitations of existing studies and make an argument for the need for future investigation on this important topic using standard verifiable instruments and utility measurements. Recent findings: Reinvigorating support for pancreas transplantation as a life-extending and quality-of-life-enhancing treatment for complicated diabetes mellitus remains a work in progress. Over the past two decades, improvements in surgical management, donor selection, recipient selection and immunosuppression have dramatically improved patient and graft outcomes, achieving durable restoration of normal glucose homeostasis in over 90% of patients. These significant advances in the field of pancreas transplantation have presumably had a positive effect on quality of life of pancreas recipients in the current era; however, this remains unconfirmed. Summary: Technical success in pancreas transplantation has improved dramatically since quality of life was last vigorously investigated in pancreas transplant recipients. Comprehensive review of the literature demonstrates the need and potential usefulness of further study substantiating quality of life benefit after pancreas transplantation, as it remains one of the primary considerations for this procedure.